2011
DOI: 10.1073/pnas.1114204109
|View full text |Cite
|
Sign up to set email alerts
|

Murine cytomegalovirus encodes a miR-27 inhibitor disguised as a target

Abstract: Individual microRNAs (miRNAs) are rapidly down-regulated during conditions of cellular activation and infection, but factors mediating miRNA turnover are poorly understood. Infection of mouse cells with murine cytomegalovirus (MCMV) induces the rapid down-regulation of an antiviral cellular miRNA, miR-27. Here, we identify a transcript produced by MCMV that binds to miR-27 and mediates its degradation. UV-crosslinking and high-throughput sequencing [CRAC (UV-crosslinking and analysis of cDNA)] identified MCMV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
118
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(123 citation statements)
references
References 42 publications
4
118
0
1
Order By: Relevance
“…similar to what has been described for Herpesvirus and cytomegalovirus. [27][28][29] However, it should be noted that the ability of bacterial pathogens to actively deliver RNAs into host cells has not been demonstrated yet.…”
Section: Emerging Principles and Open Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…similar to what has been described for Herpesvirus and cytomegalovirus. [27][28][29] However, it should be noted that the ability of bacterial pathogens to actively deliver RNAs into host cells has not been demonstrated yet.…”
Section: Emerging Principles and Open Questionsmentioning
confidence: 99%
“…25 and 26), although a mechanism by which viral RNAs mediate the direct degradation of host miRNAs has been recently unveiled. [27][28][29] Several studies have explored the impact of apicomplexan parasites, many of which cause serious diseases in humans, on host microRNA expression during infection. Interestingly, modulation of host microRNA profiles was observed upon infection with several parasites, including Cryptosporidium parvum, 30,31 Plasmodium chabaudii, 32 Toxoplasma gondii 33 and Eimeria papillata.…”
Section: Microrna Responses To Pathogenic Bacteriamentioning
confidence: 99%
“…This exciting discovery revealed "an important RNA that had flown under the radar" [129]. Another exemplary study was conducted by Libri et al [130] using CRAC. They demonstrated that an OFR of murine cytomegalovirus (MCMV), m169, acted as a miRNA sponge and mediated the degradation of miR-27 in host cells.…”
Section: Exploring Roles Of Cernamentioning
confidence: 99%
“…Furthermore comparison of these RNAs reveals little in common: HSUR-1 is a small nuclear RNA (snRNA) of 143 nt whereas m169 is a »1.7 kb spliced mRNA transcript that localizes predominantly to the cytoplasm. 19 Tailing and trimming of miRNAs: inside or outside of RISC?…”
Section: Destructive Regulators Of Mirnas: Recruiters Localizers or mentioning
confidence: 99%
“…We and others subsequently identified an MCMV transcript that directly associates with mature miR-27 and mediates its degradation. 19,20 The miR-27 binding site is within the 3 0 UTR of the m169 gene and mutation of this binding site results in virus attenuation following in vivo infection. 20 Also in 2010, a distantly related herpesvirus from squirrel monkeys, Herpesvirus saimiri (HVS), was shown to produce a small non-coding RNA, termed HSUR-1, which binds to the same cellular miRNA, and also mediates its degradation; 21 this is thought to be involved in activation and potentially transformation of T-cells.…”
Section: Introductionmentioning
confidence: 99%